Modeling of an Interleaved DC-DC Boost Converter for a Direct Model Predictive Control Strategy - Effenberger, Thomas; Borngen, Hannes; Liegmann, Eyke; Hoerner, Michael; Karamanakos, Petros; Kennel, Ralph (2022 24th European Conference on Power Electronics and Applications (EPE'22 ECCE Europe), 2022)
This paper presents a model predictive control (MPC) algorithm for interleaved dc-dc boost converters with coupled inductors. The prediction model covers the switching nature of the converter and all possible operating states. The MPC algorithm is realized in MATLAB and designed such to facilitate its real-time implementation on a field programmable gate array (FPGA) using the MATLAB HDL Coder. Open-loop measurement results demonstrate the accuracy of the system model, while the effectiveness of the controller is validated in simulation.